The Development of Mathematics Learning Activities Using a Constructivist Approach for Undergraduate Students in a Mathematics Education Program - Khum-un, Seree; Ruaengsri, Somchitra (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
The purposes of this research were to: 1) develop lesson plans learning activities by using a constructivist approach of students in a mathematics education program based on 75/75 criteria; 2) compare the mean scores of mathematical knowledge and skills; and 3) study the satisfaction of undergraduate students in a mathematics education program. The sample consisted of undergraduate students in a mathematics education program, Faculty of Education Ramkhamhaeng University, 32 students enrolled in the CMA2105 algebra for teachers in the first semester of academic year 2023 by simple random sampling. The research instruments consisted of lesson plans for study of mathematics learning activities using a constructivist approach and data collection instrument; 1) a test to measure knowledge and skills couched 2) a questionnaire on student satisfaction towards mathematics learning activities using a constructivist approach. The statistics used for data analysis were mean ( ), standard deviation (S.D.), and one-sample t-test. The findings were as follows: 1) Lesson plans learning activities by using a constructivist approach of students in a mathematics education program found that its efficiency were 83.23/78.44. It was in the setting criteria 75/75. 2) The mean score comparison of their mathematical knowledge and skills with the criterion of 75 percent showed that of their score was higher at the significance level of .05. and 3) Students’ satisfaction on mathematics learning activities was at the highest level ( = 4.38, S.D. = 0.30).